Polskie numery „Gazety Literackiej” („Литературен вестник”) – podstawowe medium w recepcji literatury polskiej - Amelia Liczewa (Postscriptum Polonistyczne)
The text outlines Poland’s authority from a political and cultural point of view, by focusing on the reception of Polish literature in one of Bulgaria’s most popular (and until recently, only one remaining) literary weekly, “Literaturen vestnik”. As well as offering western ideas, it also filled certain gaps by providing translations of some great Western authors, “Literaturen vestnik” pays due attention to the developments in Central Europe, and presents the creativity of Zbigniew Herbert, Czesław Miłosz, Ryszard Kapuściński, Olga Tokarczuk, Ryszard Krynicki, Ewa Lipska, Wisława Szymborska, Andrzej Stasiuk, Magdalena Tulli. The text also gives an account of the Polishthemed issues of “Literaturen vestnik”, dedicated to some of the abovementioned authors, as well as to feminism, the Polish NIKE literary award, the Conrad Festival in Cracow and the formation of a Polish community among Bulgarian translators and readers.